Evaluation of the use of satellite photography in determining the location and intensity changes of tropical cyclones in the Arabian Sea and the Bay of Bengal - SIKKA, D. R. (MAUSAM, 1971)
Location of tropical cyclones in the Arabian Sea and the Bay of Bengal as determined by satellite photography are compared against the ’best track’ data for the years 1965-68. Median and average vector differences between the cyclone centres determined by satellite and best track are presented separately for weak and intense vortices and the errors are found to be of comparable magnitude to those reported for the Pacific and Atlantic regions by other authors. The intensity of the tropical cyclones determined from satellite photography are also compared against the intensity as given in the weather bulletins based on conventional methods and the agreement between the two is found to be 90 per cent within one stage difference in category.